Випромiнювання точкового заряду та принцип еквiвалентностi - Ломпей, Р.Р.; Симулик, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The criterion of point charge radiation, which is invariant with respect to the choice of an arbitrary, in particular, non-inertial frame of reference within the consistent radiation theory is obtained. On this basis, the validity of the principle of equivalence of inertia and gravitation in the presence of electromagnetic processes is proved.